Strategi guru dalam mengoptimalkan bahan bekas sebagai media pembelajaran anak usia dini - Pipin, Pipin; Husain, Itsnain Alfajri; Niasari, Tanjung (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
used materials can be used as learning media if they are processed in the right way. This research aims to describe teachers' strategies for optimizing used materials as learning media for early childhood. This research was conducted at the TK Dharma Wanita Kecamatan Tinanggea Kabupaten Konawe Selatan. This research is descriptive qualitative research. The data in this research comes from primary data sources and secondary data sources. Primary data comes from two teachers, while secondary data comes from two students as well as documents related to this research idea. Data was collected through interviews, observation and documentation. Data was analyzed using reduction, display and verification. Data were validated through triangulation techniques. The results of the research show that teachers optimize used materials as learning media through several activities, namely collecting, selecting or sorting, and making. After this mechanism, the media that has been created is immediately used as learning media because the media created has been adapted to the learning theme.